Cover Picture: Defective Single‐Walled Aluminosilicate Nanotubes: Structural Stability and Mechanical Properties (ChemNanoMat 3/2016). Issue 3 (16th February 2016) - Liou, Kai‐Hsin; Kang, Dun‐Yen
Abstract : Single‐walled aluminosilicate nanotubes (AlSiNTs) are an emerging form of nanotube with mechanical strength that is expected to be on par with that of single‐walled nanotubes (SWCNTs). D.‐Y. Kang et al. developed practical models of defective AlSiNTs to enable a quantitative investigation of the relationships among defect structures as well as the structural stability and mechanical properties of AlSiNTs. The assessment employed multi‐scale computational tools: density functional theory, molecular modeling, and nanoscale continuum modeling. The developed methodology could be extended to other nanotube systems to the discovery of new high‐strength nanotube materials. More information can be found in the Full paper by D.‐Y. Kang et al. onpage 189 in Issue 3, 2016 (DOI:10.1002/cnma.201500185 ).